Effect of Mastiha supplementation on NAFLD: The MAST4HEALTH Randomised, Controlled Trial. Issue 10 (16th April 2021) - Amerikanou, Charalampia; Kanoni, Stavroula; Kaliora, Andriana C.; Barone, Angela; Bjelan, Mladen; D'Auria, Giuseppe; Gioxari, Aristea; Gosalbes, María José; Mouchti, Sofia; Stathopoulou, Maria G.; Soriano, Beatriz; Stojanoski, Stefan; et al.
Abstract : Scope: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease with poor therapeutic strategies. Mastiha possesses antioxidant/anti‐inflammatory and lipid‐lowering properties. The authors investigate the effectiveness of Mastiha as a nonpharmacological intervention in NAFLD. Methods and Results: Ninety‐eight patients with NAFLD in three countries (Greece, Italy, Serbia) are randomly allocated to either Mastiha or Placebo for 6 months, as part of a multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group clinical trial. The authors assess NAFLD severity via magnetic resonance imaging (MRI) scanning and LiverMultiScan technique and evaluate the effectiveness of Mastiha through medical, anthropometric, biochemical, metabolomic, and microbiota assessment. Mastiha is not superior to Placebo on changes in iron‐corrected T1 (cT1) and Liver Inflammation Fibrosis score (LIF) in entire patient population; however, after BMI stratification (BMI ≤ 35 kg m ‐2 and BMI > 35 kg m ‐2 ), severely obese patients show an improvement in cT1 and LIF in Mastiha versus Placebo. Mastiha increases dissimilarity of gut microbiota, as shown by the Bray‐Curtis index, downregulates Flavonifractor, a known inflammatory taxon and decreases Lysophosphatidylcholines‐(LysoPC) 18:1, Lysophosphatidylethanolamines‐(LysoPE) 18:1, and cholic acid compared to Placebo. Conclusion: Mastiha supplementation improves microbiota dysbiosis and lipid metabolite levels in patients with NAFLD, although it reduces parameters of liver inflammation/fibrosis only in severely obese patients. Abstract : NAFLD is the most common liver disease. Mastiha possesses antioxidant/anti‐inflammatory and lipid lowering properties. We designe a multicenter, randomized, double‐blind, placebo‐controlled clinical trial to explore the effectiveness of Mastiha as a nonpharmacological intervention in NAFLD. Mastiha supplementation improves microbiota dysbiosis and lipid metabolite levels in patients with NAFLD. Also, it reduces parameters of liver inflammation/fibrosis in severely obese patients.